Rosai–Dorfman‐type histiocytes occur in eosinophilic chronic rhinosinusitis and potentially play a role in disease initiation and persistence. Issue 4 (17th May 2016) - Wilsher, Mark James; Bonar, Fiona
Abstract : Aims: We recently identified the presence of Rosai–Dorfman‐type histiocytes (RDH) in sinonasal tissue removed from individuals with eosinophilic chronic rhinosinusitis (ECR). We sought to determine their clinical significance. Methods and results: Sinonasal biopsies from 10 individuals (index cases) with classical features of ECR and the additional finding of RDH were collected during a two‐and‐a‐half‐year period. Twenty‐one sinonasal biopsies with a diagnosis of ECR accrued during a 6‐month period were reviewed at one institution to assess the presence of this phenomenon in archived material. Five of the 10 index cases were recurrent; in four of these in which archival material was available, three had RDH on review. Of the 21 review cases, 52% contained RDH. Six of the review cases represented recurrent disease and in five of these RDH were demonstrable. Archival material was available from five cases that recurred, RDH being demonstrable in three. RDH were seen to persist across multiple recurrences. Conclusions: The presence of RDH within ECR samples is associated highly with recurrence. RDH have properties of antigen‐presenting cells and may play a hitherto unrecognized role in the initiation and persistence of ECR.